Formulation of Antiacne Cream Dosage Form Containing Mangosteen (Garcinia mangostana L.) Pericarp Ethanolic Extract - Supomo; Apriliana, Anita; Purnawati, Titin; Risqi, Ainur (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract. The aim of this study was to formulate ethanolic extract of mangosteen (Garcinia mangostana L.) pericarp (EEMP) in the antiacne cream dosage form. The formulae were made with 3 varied concentrations of 0.5%, 1.5% and 4.5%. The tests carried out in this study were organoleptic cream preparations (odor, color, texture), homogeneity, pH, determination of the type of cream, spreadability, and the antibacterial activity against Staphylococcus epidermidis. The results of physical property evaluations showed that the EEMP indicated the pH value of 6, the spredability of the cream increased along with the increasing length of storage time. Duncan Test on the measurement of diameter dispersibility based on storage time showed that there were significant differences between the spreadability of the cream B and C. The cream produced was easy to wash indicating oil in water (o/w) type. The results of antibacterial activity test applying agar diffusion method using Mueller Hinton medium Agar (MHA) indicated that the inhibition zones of formulae II and III were 5.2 and 6 mm, respectively. Whereas, the formula I as well as the negative control showed no inhibition zones. It can be concluded that the EEMP can be formulated as an antiacne cream. The best cream formula was the formula II with the results of physical properties test were quite stable and able to produce inhibition zone against Staphylococcus epidermidis. Keywords: Garcinia mangostana, cream, antiacne, antibacterial, Staphylococcus epidermidis.